Aerobic Exercise Moderates the Effect of Heavy Alcohol Consumption on White Matter Damage. (2nd April 2013) - Karoly, Hollis C.; Stevens, Courtney J.; Thayer, Rachel E.; Magnan, Renee E.; Bryan, Angela D.; Hutchison, Kent E.
Abstract : Background: Chronic alcohol abuse is related to numerous deleterious neurobiological consequences, including loss of gray matter, damage to white matter (WM), and impairment of cognitive and motor functions. Aerobic exercise has been demonstrated to slow cognitive decline and decrease the negative neural changes resulting from normal aging and from several diseases. It is possible that exercise may also prevent or repair alcohol‐related neurological damage. This study tested the hypothesis that aerobic exercise protects WM in anterior and dorsal areas of the brain from damage related to heavy alcohol use. Methods: Sixty individuals underwent a diffusion tensor imaging session and completed measures of alcohol consumption, loss of control over drinking, and aerobic exercise participation. Analyses examined the relationship of exercise, alcohol, and their interaction to fractional anisotropy (FA) in the superior longitudinal fasciculus (SLF), external capsule (EC), superior and anterior corona radiata, and fornix. The relationship of aerobic exercise and alcohol consumption to self‐reported loss of control over drinking were also examined. Results: A significant interaction was observed between alcohol consumption and aerobic exercise participation on FA in the SLF and EC. In the models examining loss of control over drinking, a significant interaction between aerobic exercise and alcohol consumption was observed, such that alcohol consumption was associated with loss of control more strongly for low exercisers than high exercisers. Conclusions: These results indicate that the association between heavy alcohol consumption and WM damage in the EC and SLF and the association between alcohol consumption and loss of control over drinking are greater among individuals who do not exercise regularly. These results are consistent with the notion that exercise may protect WM integrity from alcohol‐related damage.